2022
DOI: 10.3390/jof8030319
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Neofusicoccum parvum for the Production of the Phytotoxic Metabolites (-)-Terremutin and (R)-Mellein

Abstract: Two Neofusicoccumparvum isolates and a UV mutant were characterized for their phytotoxin production in vitro, their pathogenicity on grapevine, and their genome sequenced. The isolate Np-Bt67 produced high level of (-)-terremutin, but almost no (R)-mellein, and it was the most aggressive on grapevine, triggering apoplexy. Similar symptoms were not induced by purified (-)-terremutin. The isolate Bourgogne S-116 (Np-B) produced 3-fold less (-)-terremutin and high amounts of (R)-mellein, but it was less aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Six other toxins were rather more detected in the wood of apoplectic vines such as OH-tyrosol 1-O-glucoside, cis-4hydroxy-scytalone, dimethylallyl-scopoletin, terremutin, tyrosol-4sulfate, and mellein. Mellein and terremutin are especially produced by Botryosphaeriaceae species such as Neofusicoccum parvum, Diplodia seriata, or Lasiodiplodia (Andolfi et al, 2011;Abou-Mansour et al, 2015;Cimmino et al, 2017;Reveglia et al, 2019;Reveglia et al, 2021;Trotel-Aziz et al, 2022), and their detection in woody tissues was first reported by Abou-Mansour et al (2015) in the brown-striped wood of Botryosphaeria dieback-diseased vines. Our results, therefore, are consistent with those of Bruez et al (2021), who reported that these esca-expressing vines were colonized by Botryosphaeriaceae species.…”
Section: Putative Toxins Are Detected In All Wood Samples Including T...mentioning
confidence: 99%
“…Six other toxins were rather more detected in the wood of apoplectic vines such as OH-tyrosol 1-O-glucoside, cis-4hydroxy-scytalone, dimethylallyl-scopoletin, terremutin, tyrosol-4sulfate, and mellein. Mellein and terremutin are especially produced by Botryosphaeriaceae species such as Neofusicoccum parvum, Diplodia seriata, or Lasiodiplodia (Andolfi et al, 2011;Abou-Mansour et al, 2015;Cimmino et al, 2017;Reveglia et al, 2019;Reveglia et al, 2021;Trotel-Aziz et al, 2022), and their detection in woody tissues was first reported by Abou-Mansour et al (2015) in the brown-striped wood of Botryosphaeria dieback-diseased vines. Our results, therefore, are consistent with those of Bruez et al (2021), who reported that these esca-expressing vines were colonized by Botryosphaeriaceae species.…”
Section: Putative Toxins Are Detected In All Wood Samples Including T...mentioning
confidence: 99%
“…These mutants remained pathogenic on grapevine, showing that these two metabolites alone are not essential for fungal virulence. However, they could play a quantitative role in the infection process [93]. Apart from secondary metabolites, SSPs may also be involved in the induction of wood necrosis and foliar symptoms of GTD, as discussed in the above paragraph.…”
Section: Phytotoxic Effect Of Secondary Metabolites and Small Proteinsmentioning
confidence: 99%
“…Two N. parvum isolates and a UV mutant were studied for their phytotoxin production in vitro, their pathogenicity on the grapevine, and their genome sequence [ 129 ]. Essentially ( R )-mellein and (-)-terremutin were the main phytotoxins produced by the selected isolates.…”
Section: Phytotoxic Metabolites Produced By Fungi Involved In Gtds An...mentioning
confidence: 99%
“…Alternatively, ( R )-mellein and (-)-terremutin could act as a virulence factor (i.e., quantitatively increasing the disease) than as a pathogenicity factor (i.e., required to trigger the disease). To confirm this hypothesis for ( R )-mellein, mutants unable to produce PMs should be created, and their pathogenicity should be compared with their wild-type parent [ 129 ].…”
Section: Phytotoxic Metabolites Produced By Fungi Involved In Gtds An...mentioning
confidence: 99%